2023
DOI: 10.14814/phy2.15629
|View full text |Cite
|
Sign up to set email alerts
|

PTEN‐AKT pathway attenuates apoptosis and adverse remodeling in ponatinib‐induced skeletal muscle toxicity following BMP‐7 treatment

Abstract: Tyrosine kinase inhibitors (TKIs) including ponatinib are commonly used to treat cancer patients. Unfortunately, TKIs induce cardiac as well as skeletal muscle dysfunction as a side effect. Therefore, detailed mechanistic studies are required to understand its pathogenesis and to develop a therapeutic treatment. The current study was undertaken to examine whether ponatinib induces apoptosis and apoptotic mechanisms both in vitro and in vivo models and furthermore to test the potential of bone morphogenetic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
(104 reference statements)
0
3
0
Order By: Relevance
“…Subsequently, groups 1 and 2 cells received fresh growth media, while groups 3 and 4 cells received 10 μg of MSC-Exos, and cells were cultured for an additional 24 h ( Figure 1 A). After the treatment period, MTT (Roche, Indianapolis, IN, USA) was performed following the manufacturer’s protocol as previously published [ 39 ]. Briefly, MTT reagent was added to each well for 4 h at 37 °C, resulting in the formation of formazan crystal, which was then solubilized and incubated overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, groups 1 and 2 cells received fresh growth media, while groups 3 and 4 cells received 10 μg of MSC-Exos, and cells were cultured for an additional 24 h ( Figure 1 A). After the treatment period, MTT (Roche, Indianapolis, IN, USA) was performed following the manufacturer’s protocol as previously published [ 39 ]. Briefly, MTT reagent was added to each well for 4 h at 37 °C, resulting in the formation of formazan crystal, which was then solubilized and incubated overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, groups 1 and 2 cells received fresh growth media, while groups 3 and 4 cells received 10 µg of MSC-Exos, and cells were cultured for an additional 24 h (Figure 1A). After the treatment period, MTT (Roche, Indianapolis, IN, USA) was performed following the manufacturer's protocol as previously published [39]. Briefly, MTT reagent was added to each well for 4 h at 37 • C, resulting in the formation of formazan crystal, which was then solubilized and incubated overnight.…”
Section: Mtt Assaymentioning
confidence: 99%
“…The Bax/Bcl-2 ratio is positively correlated with mitochondrial outer membrane permeabilization and the induction of apoptosis [17]. Additionally, an increase in the Bax/Bcl-2 ratio is associated with muscle atrophy induced by anticancer drugs [18,19]. In our previous study, we observed that cisplatin-induced mitochondrial ROS production raised the ratio of BCL2-associated X protein (Bax) to B cell leukemia/lymphoma 2 (Bcl-2), thereby causing mitochondrial dysfunction.…”
Section: Introductionmentioning
confidence: 99%